Balancing Professional Life and Motherhood: Lived Experiences of Female English Language Teachers in Nepal - Khadka, Krishna Kumari (Rupantaran: A Multidisciplinary Journal, 2020)
Professional mothers’ responsibility regarding motherhood and a professional life management is highly confronted with gender roles whether to quit or continue the job. Understanding about the intersection between motherhood and professional life helps to navigate and negotiate the dual roles. This phenomenological study is based on qualitative method, which explores how female English language teachers are able to maintain their social and professional identity in Nepal. In this research I analyze the experiences of three secondary level female English language teachers with a focus on dual roles, multiple coping strategies and gender issues on its center. The study reveals that, balancing motherhood and professionalism as female teachers have a lot of challenges which results the incompatibility on both roles. The sensitive nature of job and inflexible and monotonous duties at home made female teachers impossible to undertake their duties perfectly at schools and at home vice –versa. Such role becomes tougher to them due to multilingual environment in the classrooms. This study can be the trajectory bridge to the professional women to get some ideas to balance motherhood and their professional lives.